Joint source-channel coded multidimensional modulation for variable-length codes - Cheng, Chen; Tu, GuoFang; Zhang, Can (Science China. Information sciences, 2014)
Resource-constrained networks such as deep space communications and mobile communications have the phenomena such us large-scale path loss,small-scale fading,and multipath effect,which are very hostile for information transmission.Combining Shannon’s source-channel coding theory with multidimensional modulation,an en/decoding method is proposed in this article called variable-length symbol-level joint sourcechannel and multidimensional modulation.Utilizing symbol-level source a priori information,an optimized symbol-level L-dimensional M-ary phase shift keying（LD-MPSK）constellation mapping function has been derived,which can increase free Euclidean distance between modulated symbols and enhance the decoding performance.It has been shown in the simulation results that the proposed scheme can achieve more than 2 dB signal-to-noise ratio gains compared with the conventional bit-level schemes under the condition of the same error rate.